2017
DOI: 10.1590/0104-07072017003010015
|View full text |Cite
|
Sign up to set email alerts
|

Use of Serious Games for Coping With Childhood Obesity: Integrative Literature Review

Abstract: Objective: was to identify studies in the scientific literature in which the serious game is used as a strategy to prevent and/or treat childhood obesity.Method: an integrative review. The search in the databases resulted in 466 studies, 17 of which were elected for analysis.Results: the use of serious games for health promotion could positively influence children's health and promote behavior changes, as well as encourage healthier habits.Conclusion: the use of serious games can be a powerful strategy for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…8 In addition, relevant studies were identified from bibliographies in relevant reviews. 8,11,12,21,[37][38][39][40][41][42] For all qualifying articles, relevant studies were identified independently by screening titles and abstracts, by one researcher and one-third by a second researcher. Next, full texts were read independently to determine final eligibility, by one researcher and one-third by a second researcher.…”
Section: Search Strategy and Eligibilitymentioning
confidence: 99%
“…8 In addition, relevant studies were identified from bibliographies in relevant reviews. 8,11,12,21,[37][38][39][40][41][42] For all qualifying articles, relevant studies were identified independently by screening titles and abstracts, by one researcher and one-third by a second researcher. Next, full texts were read independently to determine final eligibility, by one researcher and one-third by a second researcher.…”
Section: Search Strategy and Eligibilitymentioning
confidence: 99%
“…The ages ranged from 28 to 35 years, with a mean age of 31.7 years. The tool used to assess the game is a semistructured questionnaire for educational games called EGameFlow, 19 which, according to the authors, is a version of the GameFlow tool for educational games. Its main function is to assess the level of satisfaction the users experience during the game accurately and precisely.…”
Section: /12mentioning
confidence: 99%
“…The final version of the instrument contains 42 items allocated in eight dimensions: Concentration (6 items); Goal clarity (4 items); Feedback (5 items); Challenge (6 items); Control (7 items); Immersion (7 items); Social interaction (6 items); Knowledge improvement (7 items). 19 The categories with the highest averages were Goal clarity and Knowledge improvement, while the lowest averages were for Challenges and Autonomy.…”
Section: /12mentioning
confidence: 99%
“…The use of smartphones as educational technology is still limted in the literature, however, its adoption as the main interface for the user, will allow the development of games that can connect healthy habits and promote physical activities in the dynamics of a game. 23 A review study 24 aiming to identify [articles in the scientific literature that used the serious game strategy, an inactive game that focuses on the persuasive aspect to change behaviors, in the prevention and / or treatment of childhood obesity, found that there were limited publications in Brazil during the initial selection and after the analysis of the studies no Brazilian study was included, evidencing a gap in the scientific literature, highlighting the importance of more research on the subject, given its relevance to the promotion of self-care.…”
Section: /13mentioning
confidence: 99%